'Light‐Up' AIE‐Active Materials: Self‐Assembly, Molecular Recognition and Catalytic Applications. Issue 2 (26th November 2020) - Kaur, Mandeep; Kaur, Harpreet; Kumar, Manoj; Bhalla, Vandana
Abstract: Aggregation induced emission enhancement (AIEE) is one of the most widely explored phenomena to develop 'light up' (fluorescent) materials having potential applications in the field of supramolecular chemistry, analytical chemistry and material chemistry. By applying the principles of host‐guest chemistry, we have developed a variety of aggregation induced emission (AIE/AEE) active materials having specific affinity for metal ions, electron deficient/electron rich analytes. The interactions between AIE active assemblies and metal ions are further tuned to prepare nanohybrids having potential applications as catalytic/photocatalytic systems in various organic transformations under eco‐friendly conditions. This account summarizes various design strategies developed in our labortary for the preparation of AIE/AEE active building blocks having sensing and catalytic applications. Abstract : This review summarizes development of a variety of AIE‐active materials having specific affinity for different analytes for efficient molecular recognition and catalysis/photocatalysis.